A preliminary study of gut dysbiosis in children with food allergy. Issue 12 (2nd December 2017) - Inoue, Ryo; Sawai, Toshihiro; Sawai, Chihiro; Nakatani, Masako; Romero-Pérez, Gustavo A; Ozeki, Motoyuki; Nonomura, Kazuo; Tsukahara, Takamitsu
Abstract: Gut microbiota of food allergic children was analyzed by high throughput 16S rRNA gene sequencing. Signs of gut dysbiosis, which is likely associated with gut inflammation, was observed in children with food allergies. For example, decreased abundance of genus Akkermansia but increased abundance of Veillonella was found in children with food allergy in comparison with healthy control children.